2012
DOI: 10.1039/c1an15810d
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall gold nanoparticles for highly specific isolation/enrichment of N-linked glycosylated peptides

Abstract: In recent years, gold nanoparticles have been increasingly utilized as a promising material for biomedical analysis. We report here for the first time the synthesis of ultrasmall gold nanoparticles with core diameter of 1.2 nm functionalized with hydrazide groups and their use in isolation/enrichment of N-glycosylated peptides. Hydrazide-functionalized gold nanoparticles showed excellent stability in biological samples and exhibited a large capacity for peptide capturing. The captured peptides from tested stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Besides proteins, metal NCs were also applied for detection of other important biomolecules. For example, Tran et al reported the first method to use the ultrasmall Au NCs in isolation/enrichment of N ‐glycosylated peptides. Hydrazide‐functionalized Au NCs exhibited a large capacity for glycoproteins capturing.…”
Section: Metal Ncs For Biosensor Developmentmentioning
confidence: 99%
“…Besides proteins, metal NCs were also applied for detection of other important biomolecules. For example, Tran et al reported the first method to use the ultrasmall Au NCs in isolation/enrichment of N ‐glycosylated peptides. Hydrazide‐functionalized Au NCs exhibited a large capacity for glycoproteins capturing.…”
Section: Metal Ncs For Biosensor Developmentmentioning
confidence: 99%
“…Hydrazide‐functionalised AuNPs were found to be very stable in biological samples (Fig. ) . In addition, they exhibit unique solubility and large capacity for the capture of peptides, demonstrating great potential for the capture of target N ‐linked deglycosylated peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Schematic illustration of glycopeptide capture using A u 25 NP . (A) Hydrazide functionalisation of glutathione‐protected A u 25 NP . (B) Glycopeptide‐capturing procedure.…”
Section: Methods Based On Other Separation Techniquesmentioning
confidence: 99%
“…For example, the match in the size of these NPs to proteins [6] , multi helix DNA bundle structures [7] , and nuclear pores [8] is ideal for engineering biomolecule-NP interactions and targeting the cell nucleus; their high biocompatibility is maintained even after they are endocytosed by cells [9] ; their large surface-to-volume ratio provides high payload efficiency [10] ; and their strong diffusivity enables them to penetrate the blood–brain barrier [11] and solid tumor tissues [12] . These properties make sAuNPs excellent vehicles for various applications including biosensor [13] , [14] , [15] , drug/gene delivery [16] , [17] , [18] , and cancer therapy [19] .…”
Section: Methods Detailsmentioning
confidence: 99%